Dual Fe/Pd‐Catalyzed Reductive Cross‐Coupling: Constructing gem‐Difluoroallylenes with Alkenyl Bromides and Bromodifluoromethanes. Issue 48 (22nd December 2021) - Li, Tao; Luo, Yuhang; Wu, Zefeng; Xiao, Tiebo; Jiang, Yubo; Qin, Guiping
Abstract: Reported herein is an unprecedented dual iron/palladium‐catalyzed reductive cross‐coupling of alkenyl bromides and bromodifluoromethanes with manganese as the reductant. This methodology leads to the efficient construction of a series of gem ‐difluoroallylenes under mild reaction conditions without requiring the addition of stoichiometric amounts of catalyst. Preliminary mechanism investigations indicate that the radical pathway might not be involved in this novel dual transition metal catalyzed reaction. Abstract : An unprecedented iron/palladium‐catalyzed reductive cross‐coupling of alkenyl bromides and bromodifluoromethanes with manganese as the reductant has been disclosed. A variety of functional groups was well tolerated, providing various substituted gem ‐difluoroallylenes in moderate to good yields. The preliminary mechanism studies ruled out the radical pathway for this new reaction.